2005
DOI: 10.1159/000084607
|View full text |Cite
|
Sign up to set email alerts
|

Dilution Method to Refold Bacterially Expressed Recombinant Der f 2 and Der p 2 to Exhibit the Secondary Structure and Histamine-Releasing Activity of Natural Allergens

Abstract: Background: Structurally refolded recombinant forms of major house dust mite group 2 allergens, Der f 2 and Der p 2, expressed in Escherichia coli, were prepared by solubilizing the insoluble products with urea and subsequently dialyzing against buffer. In this study, we determined conditions for refolding the urea-denatured recombinant Der f 2 and Der p 2 by one-step dilution as an alternative to dialysis, which requires several steps of handling and much time and cost. Methods: The insoluble bacterial produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…An ELISA simply using the enhancer solutions, which obtains remarkably strengthened signals for allergen-specific IgE, would be useful for the study of allergies with murine models. In addition, this paper showed that recombinant forms of the major mite allergens Der p 1, Der f 1 [12,13,14,15,16,17, 23] and Der f 2 [18,19,20, 24] can elicit a significant allergen-specific IgE response in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ELISA simply using the enhancer solutions, which obtains remarkably strengthened signals for allergen-specific IgE, would be useful for the study of allergies with murine models. In addition, this paper showed that recombinant forms of the major mite allergens Der p 1, Der f 1 [12,13,14,15,16,17, 23] and Der f 2 [18,19,20, 24] can elicit a significant allergen-specific IgE response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As the B cell epitopes for recombinant forms with and without hyperglycosylation are considered to be equivalent [12, 13], we used the hyperglycosylated Der p 1-WT and Der f 1-WT for detecting Der p 1- and Der f 1-specific Abs as alternatives to the unglycosylated rDer p 1 and rDer f 1, whose production is much lower than that of the hyperglycosylated forms in yeast [16]. Recombinant Der f 2 (rDer f 2) was prepared as previously described [18] and used for immunization and the coating of microtiter plates for ELISA for Der f 2-specific Abs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 and 49), and a recombinant form of a mite major group 2 allergen, Der f 2 (50). A precursor form of rDer f 1-C35S was prepared by site-directed mutagenesis, secreted into the yeast culture supernatant, and converted to its mature form by yeast-derived protease activity within the supernatant by dialysis with an acidic buffer (48).…”
Section: Cystatin a And Recombinant Allergensmentioning
confidence: 99%
“…After the dilution, the concentration of cystatin A was 500 ng/ml. The method used to measure the amount of histamine released from basophils was as described previously (19,50). Effective concentrations yielding half-maximal allergen response were determined from curves in the histamine-releasing assay by using Prism version 4.0 (GraphPad).…”
Section: Histamine Release From Human Basophilsmentioning
confidence: 99%